Optimization of Competence Through Training Programs in the Implementation of Occupational Health and Safety Practices: Optimalisasi Kompetensi Melalui Program Pelatihan Pada Penerapan Praktik Kesehatan dan Keselamatan Kerja - Emilisa, Netania; Yusran, Husna Leila; Masnita, Yolanda; Tanuwijaya, Justine (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
The objective of this activity is to evaluate the effectiveness of the training program in enhancing participants' competence in the implementation of occupational health and safety (OHS) practices. The method used in this activity involves a competency test for 20 vocational school teachers who are members of P4 West Jakarta. The training program includes the comprehensive delivery of OHS material, intensive training, and evaluation through pre-tests and post-tests to measure competency improvement. The results show that the training program has a significant impact on improving participants' competence. A total of 80% of participants were declared competent in each test unit after undergoing the training, while 20% of participants still did not meet the expected competency. This improvement reflects the success of the teaching methods and training materials applied. The sustainability of this training program requires further evaluation and additional support for participants who have not yet achieved the expected competency. These efforts are crucial to ensure that all participants can meet the desired competency standards. The findings of this study provide strong evidence that a structured and comprehensive training program can effectively enhance competence in OHS practices. Additionally, the importance of continuous evaluation and adjustment of the training program is highlighted to improve the program's effectiveness and quality in the future. Thus, this study concludes that the training program implemented is effective in increasing participants' competence in OHS practices, but continuous efforts are needed to improve the competence of participants who have not yet met the standards.